Implementasi Encounter Record untuk menangani Flood Attack pada Routing Protocol Epidemic dan Routing Protocol Spray-And-Wait DTN - Yefta Kristiyanto; Rakhmadhany Primananda; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Delay Tolerant Network (DTN) is a network architecture that can be applied in areas that have a delay But. DTN has limits on its network storage size. DTN has two routing protocols, single-copy and multi-copy routing. In multi-copy, resources become full faster because they are used to store message replicas and its becomes more vulnerable to flood attacks than single-copy routing protocol. Flood attack is an attack from a malicious node by sending a huge number of packets into the network. Encounter records are one of many security mechanism that can be used to detect flood attack on DTN. In this research, ER development was carried to handle flood attack. The time needed to detect flood attacks in Epidemic is 1.22349 seconds and in Spray-and-wait routing is 0.97765 second. The accuracy of detection using ER is more than 80% for both protocols. Difference of PDR result of using ER and without ER in Epidemic 17.209% and in Spray-and-wait is 66.7139%. The average latency in epidemic routing is 2774.35489 ms and in spray-and-wait routing is 2794.70716 ms. The result of overhead ratio in epidemic routing is 281.52343 and in Spray-and-wait routing is 8.82161.